On the Ancestral UDP-Glucose Pyrophosphorylase Activity of GalF from Escherichia coli - Ebrecht, Ana C.; Orlof, Agnieszka M.; Sasoni, Natalia; Figueroa, Carlos M.; Iglesias, Alberto A.; Ballicora, Miguel A. (Frontiers in Microbiology, 2015)
In bacteria, UDP-glucose is a central intermediate in carbohydrate metabolism. The enzyme responsible for its synthesis is encoded by the galU gene and its deletion generates cells unable to ferment galactose. In some bacteria, there is a second gene, galF, encoding for a protein with high sequence identity to GalU. However, the role of GalF has been contradictory regarding its catalytic capability and not well understood. In this work we show that GalF derives from a catalytic (UDP-glucose pyrophosphorylase) ancestor, but its activity is very low compared to GalU. We demonstrated that GalF has some residual UDP-glucose pyrophosphorylase activity by in vitro and in vivo experiments in which the phenotype of a galU- strain was reverted by the over-expression of GalF and its mutant. To demonstrate its evolutionary path of “enzyme inactivation” we enhanced the catalysis by mutagenesis and showed the importance of the quaternary structure. This study provides important information to understand the structural and functional evolutionary origin of the protein GalF in enteric bacteria.